Evaluasi Kinerja Dan Pengalaman Pengguna Websitepartai Gerindra Menggunakan Metode Web Usability Testing - Arif Yuliawan; Agus Budiyantara (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to evaluate the performance and user experience of the Gerindra Party’s official website using Web Usability Testing. A quantitative descriptive approach was adopted with 31 respondents, utilizing Likert-scale questionnaires and task-based observations. The evaluation covered five key aspects: effectiveness, efficiency, user satisfaction, readability, and security & reliability. Results showed good usability, with average scores ranging from 3.80 to 4.07 out of 5. Specifically, effectiveness scored 3.80, efficiency 3.92, satisfaction 4.07, readability 3.98, and security 4.01. However, issues such as non-intuitive navigation, slow loading speed, and inconsistent interface design were identified. These findings suggest that while the website meets usability standards, there is still room for improvement to enhance the overall user experience. Improvement recommendations include: (1) simplifying menu structures, (2) optimizing technical performance to improve speed, and (3) enhancing interface design consistency for better usability. The study’s findings provide a solid foundation for upgrading the website, making it a more effective digital political communication tool.